Short-term outcomes of combined neuraxial and general anaesthesia versus general anaesthesia alone for elective open abdominal aortic aneurysm repair: retrospective population-based cohort study†. (May 2020) - Salata, Konrad; Abdallah, Faraj W.; Hussain, Mohamad A.; de Mestral, Charles; Greco, Elisa; Aljabri, Badr; Mamdani, Muhammad; Mazer, C. David; Forbes, Thomas L.; Verma, Subodh; Al-Omran, Mohammed
Abstract: Background: Use of neuraxial anaesthesia for open abdominal aortic aneurysm repair is postulated to reduce mortality and morbidity. This study aimed to determine the 90-day outcomes after elective open abdominal aortic aneurysm repair in patients receiving combined general and neuraxial anaesthesia vs general anaesthesia alone. Methods: A retrospective population-based cohort study was conducted from 2003 to 2016. All patients ≥40 yr old undergoing open abdominal aortic aneurysm repair were included. The propensity score was used to construct inverse probability of treatment weighted regression models to assess differences in 90-day outcomes. Results: A total of 10 447 elective open abdominal aortic aneurysm repairs were identified; 9003 (86%) patients received combined general and neuraxial anaesthesia and 1444 (14%) received general anaesthesia alone. Combined anaesthesia was associated with significantly lower hazards for all-cause mortality (hazard ratio [HR]=0.47; 95% confidence interval [CI], 0.37–0.61) and major adverse cardiovascular events (HR=0.72; 95% CI, 0.60–0.86). Combined patients were at lower odds for acute kidney injury (odds ratio [OR]=0.66; 95% CI, 0.49–0.89), respiratory failure (OR=0.41; 95% CI, 0.36–0.47), and limb complications (OR=0.30; 95% CI, 0.25–0.37), with higher odds of being discharged home (OR=1.32; 95% CI, 1.15–1.51). Combined anaesthesia was also associated with significant mechanical ventilation and ICU and hospital length of stay benefits. Conclusions: Combined general and neuraxial anaesthesia in elective open abdominal aortic aneurysm repair is associated with reduced 90-day mortality and morbidity. Neuraxial anaesthesia should be considered as a routine adjunct to general anaesthesia for elective open abdominal aortic aneurysm repair.